Alternative pathway activation: Ever ancient and ever new. Issue 1 (11th September 2022) - Liszewski, M. Kathryn; Atkinson, John P.
Summary: Primitive underpinnings of the alternative pathway (AP), namely, a C3‐like protein, likely arose more than a billion years ago. The development of an AP amplification loop, while greatly enhancing speed and potency, also presents a double‐edged sword. Although critical to combat an infectious disease, it is also potentially destructive, particularly in a chronic disease process involving vital organs where scarring and reduction of regulatory function can occur. Furthermore, new knowledge is pointing to genetic factors involved in an increasing number of complement‐related diseases such as age‐related macular degeneration. However, even a normal functioning repertoire of complement components can drive cellular damage as a result of low‐level complement activation over time. Thus, the modern human AP now faces a new challenge: cumulatively‐driven tissue damage from chronic inflammatory processes that mediate cellular injury. The impact of ongoing low‐level AP‐enhanced complement activation in disease processes is just beginning to be appreciated and studied. However, the sheer numbers of individuals affected by chronic diseases emphasize the need for novel therapeutic agents capable of modulating the AP. The more we learn about this ancient system, the greater is the likelihood of developing fresh perspectives that could contribute to improved human health.